(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The fashion industry e-commerce has witnessed a remarkable increase in market, leading to significant changes in online consumer behaviour. Consequently, research in the field of consumer online behaviour in the fashion industry has become highly relevant for marketers and online retailers. It is essential for fashion-industry e-commerce businesses to gain a deeper understanding of the barriers that hinder customers from making online purchases, comprehend the mechanisms of these barriers, and their role in making purchase decisions. This study aims to provide an overview and analysis of the barriers to online purchase in the fashion industry e-commerce, classify these barriers and determine the role that each barrier plays in making a purchase decision. The research methodology involves both qualitative and quantitative research methods, including the collection of secondary and primary descriptive data. The research approach included empirical and theoretical research levels with the application of abstraction, analysis, synthesis, deduction methods, and consumer surveys. The study identified five main groups of barriers to online purchase in the fashion industry e-commerce, which are technological barriers, privacy and financial risk barriers, barriers related to the limitations of the online shopping process, delivery-related barriers, and barriers linked to difficulties in returning goods. After surveying 147 respondents, mean values, median, standard deviation, skewness, and variance were calculated for each barrier. Additionally, a two-dimensional bar chart was designed to display the barriers and their mean values, organized in the order from the ones with the most negative impact on purchase decisions to the least. The findings revealed that the most significant and common barriers to online purchase in the fashion industry e-commerce are difficulty in searching for products, trial inconvenience, long delivery times, payment difficulties, and delivery costs. This knowledge is useful for e-shops to provide high-quality customer experience and service, predict changes in behaviour and trends, develop marketing tools and strategies to overcome barriers to purchase, and ultimately increase loyalty and sales.